The Wraith of Childhood: How Contemporary TV Series Set the Origin of Characters’ Vulnerability—and of Creative Developments—On Childhood Trauma - Boni, Marta (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
This article explores how contemporary television series use childhood as both a narrative and affective device to revisit trauma, vulnerability, and emotional complexity. Drawing on affect theory, intermediality, and cultural analysis, it examines how “minor feelings” emerge in serial storytelling. Rather than portraying childhood as a space of innocence, the article highlights its role as a site of conflict, memory, and unresolved tension. Focusing on the use of toys as vectors of memory, it analyzes flashbacks as tools to represent fractured temporality and the lasting impact of early emotions on adult subjectivity. Using the Quebec television series In Memoriam (Crave, 2024) as its central case study, the paper shows how toys can trigger traumatic recall and illuminate ongoing psychic wounds. Television’s capacity for repetition allows these minor feelings to circulate within spaces of nostalgia and unease, often mobilizing the uncanny. The paper argues that TV functions as a mobile archive of feelings, shaping how viewers engage with both personal and collective pasts.